Women’s quest for identity in the selected works of Anita Desai & Shashi Deshpande - Rahman, Md. Towhidur (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2016.